Dukungan Keluarga dan Petugas Kesehatan Berhubungan dengan Pemberian ASI Eksklusif - Eksadela, Monika; Syukri, Muhammad; Fitri, Adelina (Jurnal Bidan Cerdas, 2021)
Background: The coverage of exclusive breastfeeding in Hiang Health Center Working Area in 2019 was 49.1%. Purpose: This study aimed to determine the relationship between family and health worker support with exclusive breastfeeding at the Hiang Health Center, Kerinci Regency Methods: This study used a cross-sectional design with a sample of 165 people. Samples were taken using proportional random sampling technique. The samples taken were mothers who had children aged 6-23 months with the mother's condition physically healthy, able to read, write and speak Indonesian, did not suffer from serious diseases that harm the baby when breastfeeding, such as HIV, Active TB, and Hepatitis. Data collection was carried out from April to May 2021 with the interview method using a structured questionnaire. Data processing was carried out univariate and bivariate using chi-square test. Results: The proportion of children who did not get exclusive breastfeeding was 45.5%. Bivariate analysis showed that family support (p=0.004 OR= 1.68 95%CI 1.2-2.3), and support from health workers (p=0.000 OR=2.42 95% CI 1.73 - 3.37) were associated with exclusive breastfeeding. Conclusion: Family and the health workers support were associated with exclusive breastfeeding.